2004
DOI: 10.1046/j.0001-690x.2003.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the peer‐taught 12‐week family‐to‐family education program for severe mental illness

Abstract: This study provides evidence that FFEP is helpful to relatives of persons with SMI by reducing subjective burden and worry, and increasing empowerment, knowledge about SMI, understanding the mental health system, and self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 20 publications
8
98
0
4
Order By: Relevance
“…The results of this study can be used to prospectively identify caregivers at risk for adverse health outcomes associated with caregiving and target them for a prevention-focused intervention. A number of peer and clinician-administered interventions for family caregivers of patients with bipolar and other serious mental disorders [e.g., The Family to Family program offered by the National Alliance for the mentally ill (Dixon et al, 2004);Multiple Family Group (McFarlane, 1983), Family Psychoeducation for bipolar disorder (Miklowitz, et al, 2000)] and other family interventions with demonstrated clinical efficacy, include material on caregiver self-care, and might be offered to caregivers with high burden profiles. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study can be used to prospectively identify caregivers at risk for adverse health outcomes associated with caregiving and target them for a prevention-focused intervention. A number of peer and clinician-administered interventions for family caregivers of patients with bipolar and other serious mental disorders [e.g., The Family to Family program offered by the National Alliance for the mentally ill (Dixon et al, 2004);Multiple Family Group (McFarlane, 1983), Family Psychoeducation for bipolar disorder (Miklowitz, et al, 2000)] and other family interventions with demonstrated clinical efficacy, include material on caregiver self-care, and might be offered to caregivers with high burden profiles. …”
Section: Discussionmentioning
confidence: 99%
“…Although caregivers who internalize the devaluing views of society might be anticipated to experience a decrement in self-esteem, less adaptive coping, and inadequate health practices, a response of "righteous anger" may motivate them to take constructive actions to reduce the adverse impact of stigma, such as participating in consumer advocacy programs which promote empowerment and social support, and have been associated with improved caregiver health outcomes (Dixon et al, 2004).…”
Section: Stigmatized Caregiversmentioning
confidence: 99%
“…(35) Estudos realizados em diferentes países mostram que a psicoeducação fornece aos cuidadores níveis elevados de satisfação, diminui o cargo familiar, promove maior aderência e aceitação do paciente ao tratamento, reduz a preocupação e frustração do cuidador e diminui os níveis de recaídas e reinternações hospitalares. (16,(36)(37)(38)(39)(40) Apesar da sua natureza crônica e incapacitante e dos altos níveis de incidência populacional, ainda é escasso o número de estudos sobre participação familiar e apoio impactante no tratamento de pacientes com transtornos de ansiedade. Porém, resultados de pesquisas relacionados a sintomas compulsivo-obsessivos e estresse pós-traumático (41) confirmam que a participação familiar é eficaz no tratamento daqueles pacientes.…”
Section: Psicoeducação E Família: Visão Geral Atual E Perspectivas Deunclassified
“…Each item was rated from 1 (not true at all) to 5 (very true), resulting in a sum score of 12 to 60, with higher scores indicating greater empowerment. This subscale has been shown to be sensitive to change in a study examining a family intervention [27]. Family members' perceived efficacy to carry out tasks targeted by the intervention was assessed with a 7-item measure, adapted from the initial Family of Heroes study [23].…”
Section: Methodsmentioning
confidence: 99%